Human Resource Management and Technological Challenges - Machado, Carolina; Davim, J. Paulo (Management and Industrial Engineering,, 2014)
This book focuses on the challenges and changes that new technologies bring to human resources (HR) of modern organizations. It examines the technological implications of the last changes taking place and how they affect the management and motivation of human resources belonging to these organizations. It looks for ways to understand and perceive how organizational HR, individually and as a team, conceptualize, invent, adapt, define and use organizational technology, as well as how they are constrained by features of it. The book provides discussion and the exchange of information on principles, strategies, models, techniques, methodologies and applications of human resources management and technological challenges and changes in the field of industry, commerce and services.